2019
DOI: 10.1111/jcpp.13051
|View full text |Cite
|
Sign up to set email alerts
|

Childhood gender‐typed behavior and emotional or peer problems: a prospective birth‐cohort study

Abstract: Background Retrospective and cross‐sectional studies often report associations between childhood gender nonconformity and greater emotional and peer difficulties. This study used the ALSPAC birth cohort to investigate relationships between childhood gender‐typed behavior and peer and emotional problems throughout childhood and adolescence. Methods A total of 11,192 participants had at least one measure of parent‐rated gender‐typed behavior in infancy; 7,049 participants had a measure of child‐rated gender‐type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The latter perceived abuse as "rarely" occurring, while females perceived it as "never" occurring (OR = 0.260). There is little literature on the subject, but this difference between sexes may be due to the fact that males and females have a different understanding of the violence model [57], though such understanding is currently changing. Moreover, some authors state that aggressiveness is stronger in males and abuse is more frequent in a male environment, which makes them detect it more frequently, so rejection, margination, and exclusion are less detected and more restricted to the female environment [58].…”
Section: Discussionmentioning
confidence: 99%
“…The latter perceived abuse as "rarely" occurring, while females perceived it as "never" occurring (OR = 0.260). There is little literature on the subject, but this difference between sexes may be due to the fact that males and females have a different understanding of the violence model [57], though such understanding is currently changing. Moreover, some authors state that aggressiveness is stronger in males and abuse is more frequent in a male environment, which makes them detect it more frequently, so rejection, margination, and exclusion are less detected and more restricted to the female environment [58].…”
Section: Discussionmentioning
confidence: 99%
“…These differences suggest large cross-cultural resemblances with some temporal and cultural variations in prevalence and levels of GV. Gender-variant children are at risk of a wide range of challenges to psychological well-being, in both clinical and community samples (Egan & Perry, 2001;Steensma et al, 2014;van Beijsterveldt et al, 2006;van der Miesen et al, 2018;Wallien et al, 2010;Warren et al, 2019;Yunger et al, 2004). Studying GV in community samples provides an estimate of psychological well-being that is less confounded by the distress associated with receiving a clinical diagnosis (MacMullin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, community children and adolescents who display elevated GV showed decreased psychological well-being, including internalizing and externalizing problems (van Beijsterveldt et al, 2006; van der Miesen et al, 2018; Yunger et al, 2004), poorer peer relations (Egan & Perry, 2001; Yunger et al, 2004), and lower self-worth (Egan & Perry, 2001; Yunger et al, 2004). Studies that reported assigned sex differences in how GV or GD correlated with psychological well-being usually found boys to be more affected, for instance in terms of emotional and peer challenges (Steensma et al, 2014; Wallien et al, 2010; Warren et al, 2019). As much of the research focused on mental and social challenges, less is known about general life satisfaction or happiness in children who display GV or GD.…”
mentioning
confidence: 99%
“…On the other hand, Chapman et al [36] documented the prevalence of psychological and depressive disorders in children exposed to abuse. A number of studies [12,32] coincide that the most important element in the detection of these clinical manifestations is to take into account the aforementioned characteristics, together with discrepancies between the clinical data and the story told; suspicious behavior on the part of the parents; the behavior of the child with emotional problems [34,35]; and the presence of bilateral injuries in different stages of healing or with a specific pattern indicative of abuse [22]. Victims of CA are scantly cooperative in the dental clinic [20], and are at an increased risk of suffering emotional and psychological disorders [33,35] in both childhood and adult life.…”
Section: Authoryear/type Of Studymentioning
confidence: 99%